Effects of pharmacological compounds on the barnacle larval development, metabolism and settlement. (February 2017) - Al-Aidaroos, Ali M.; Satheesh, S.; Devassy, Reny P.
Abstract: Effects of select pharmacological compounds, with known mode of action in vertebrates, were evaluated on the development, metabolism and settlement of larvae of the common fouling barnacle, Amphibalanus amphitrite . Atrovastatin, a lipid-regulating compound, cetrizine hydrochloride, an anti-histamine, atenolol, a β-blocker, and amlodipine, a calcium-channel blocker were the compounds studied. Nauplii treated with these compounds took more days to reach the cypris stage when compared with the control. These compounds also inhibited the settlement of cyprids on Petri dishes. While exposure to these compounds led to a decrease in the metabolic activity of stage III nauplii, it increased the respiratory rate of cyprids. The results emphasize the role of neurotransmitters and lipids in the development and settlement of barnacle larvae on hard surfaces. Highlights: Barnacle nauplii treated with pharmacological compounds took more days to reach the cypris stage. Treatment with pharmacological compounds also inhibited the settlement of cyprids on Petridishes. Barnacle nauplii treated with most of the pharmacological compounds showed a decrease in metabolic activity. Respiration rates showed an increase in cyprids when exposed to pharmacological compounds.